Capítulos do consumo – a recepção de telenovelas brasileiras em Cuba - Dhein, Gustavo (2018)
This thesis is a study about the reception (the ways to see and read, to decode a specific text, crossed by the living conditions of the individual) and the consumption (how context affects the media experience and how this in turn interferes in agents' practices in this same scenario) of Brazilian telenovelas in Cuba. Our main purpose is to investigate the ways in which the Cubans interpret and make use of the content of media product and how (and if) it crosses/reorganizes lifestyles ("unconscious class identities‖) in the Caribbean country. Justify this work: the durability and popularity of the Brazilian telenovelas in Cuba; the few number of academic researches about the reception of Brazilian cultural products in other countries; the also rare intellectual production interested in studying the relationship between class, reception and consumption; and, fundamentally, the idiosyncrasies of the Caribbean country, resulting from the maintenance of a (self-proclaimed) socialist system during the five last decades. As a result of this uniqueness in the western capitalist context, Cuba presents contrasts as, for example, the registration of indicators that are similar to those of developed countries in areas such as health and education, and a chronic deficiency of supply of various items, from food to technology. The low purchasing power between the Cubans combined with the restrictions of access to material and symbolic goods has converted consumption in a "lucha" (―fight‖) in which the Cubans are involved every day. In this context, the media in general - and television programs and telenovelas in particular – work as ―windows and bridges‖ that allows residents of the island to contact lifestyles and desirable things that are rarely on offer or available in their country. The television programs also contribute to insert the population of the Island into an "international popular culture" (ORTIZ, 1994) in which the hegemonic values are in contradiction to the ideal of "a new socialist man", disseminated in the local official discourse. Media products also contribute to the building of fences that delimit, with increasing emphasis, the classist differences in Cuba. Our research is conducted based on the theoretical contributions of Pierre Bourdieu (especially his concepts of habitus, capital and lifestyle), Stuart Hall (Encoding/decoding), Martín-Barbero (Theory of the Mediations), and Néstor García-Canclini (the sociocultural perspective of consumption). The corpus analyzed were telenovelas already broadcasted in Cuba. In-depth interviews and ethnographic work on the Island were also conducted over nine months of field research. As results, we identified that telenovelas, as already indicated earlier studies, do not contribute to the critical analysis of inequality, are adopted by the islanders as a way of achieving a "distance" from social reality and, especially today, reinforce a neoliberal hegemonic message (which is essentially meritocratic) that is (re) produced in the reflections and practices of agents on the Island (as in any other part of the world), despite of the local idiosyncrasies, which include, among other things, a supposed alignment with socialism six decades ago and a high cultural capital, well distributed among the population. With regard to increasing inequality (economic, priority), easily perceived in Cuba, it appears increasingly as "natural" to the Cubans and, regardless of their class condition, none of the respondents seems to know what their "real dimension" is, whether in fiction or in reality, or to have an idea about how - and if - it should - or can - be overcome, which also is translated into rather uncritical and similar readings about Brazilian soap operas. Finally, if it is a hard exercise to try to "classify" classes in Cuba, one can say that the "future" dream of each of the participants is very close to that which "democratically" spread throughout the world: that of consumption, expressed in demands for "more comfort", which means "more access to material and immaterial goods".